PENGEMBANGAN WEBSITE PORTOFOLIO DIGITAL SEBAGAI ALAT EVALUASI PADA PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Muhammad Fajar Al Kausar; Dadan Djuanda; Prana Dwija Iswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study developed a digital portfolio website as an evaluation tool for Indonesian language learning in elementary schools. The background was the limitations of teachers in finding effective and efficient evaluation media that could collect student work on the four language skills. The study used the Four-D model (Define, Design, Develop, Disseminate) with data obtained through interviews and questionnaires. Validation by evaluation experts and language experts showed the categories "Very Appropriate" and "Appropriate" without revision. The trial on 32 fifth-grade students of SDN Cileutik resulted in a score of 92.5% (category "Very Appropriate"). This website facilitates teacher evaluation, increases student engagement, and provides structured learning documentation, making it suitable for use as an innovative solution in evaluating Indonesian language learning in elementary schools.